Lacustrine Groundwater Discharge Through Giant Pockmarks (Lake Neuchatel, Switzerland) - Wirth, Stefanie B.; Bouffard, Damien; Zopfi, Jakob (Frontiers in Water, 2020)
Pockmarks are circular depressions on the floor of oceans and lakes and constitute potential hot spots of gas ebullition and/or groundwater discharge. Marine pockmarks are well studied, whereas lacustrine pockmarks are virtually unexplored. In Lake Neuchatel (Switzerland) four giant pockmarks of 80 to 150 m in diameter are located along the northern shore and adjacent to the karst system of the Jura Mountains. Two pockmarks have a ~60 m-deep chimney filled with mud; two are funnel-shaped 12 m and 29 m deep holes. We present evidence for the presence of groundwater in the pockmark chimneys and active lacustrine groundwater discharge (LGD) at both pockmark types. Temperature, electrical conductivity and calcium concentrations of the pore water in the chimneys show values typical for karst water (maximal sampling and profiling depth: 41 m into the pockmark) and contrast strongly with the properties of the lake water. TOC and TIC indicate that the chimney mud is homogenized and composed of liquefied sediments from the entire deglacial to Holocene lacustrine sediment succession. Mini mud volcanoes apparent on the suspension surface imaged with a remotely operated vehicle (ROV) localize the groundwater exit points and confirm LGD. LGD is further corroborated by electrical conductivity anomalies detected above the lutoclines and within a funnel-shaped pockmark during the ROV survey. We conclude that the giant pockmarks in Lake Neuchatel represent a type of subaquatic springs that connect the water body of the lake with the karst system. A next essential research step will be to quantify LGD via the pockmarks in order to assess their lake-wide relevance. This study underlines the existing need for research on the connectivity of lakes and oceans with groundwater systems for completing our understanding of the hydrological cycle.